Anterior Transcervical Lag Screw Fixation of Type II Odontoid Fracture - Shrestha, Dinuj; Shrestha, Pratyush (Nepal Journal of Neuroscience, 2020)
Odontoid fracture comprises approximately 20% of all cervical spine fractures. Among them type II fracture accounts for about 65-74%. Presently, direct anterior screw fixation is considered to provide successful outcome with fracture healing of 80% and also preserve C1/C2 rotation movement with benefit of early mobilization and rapid return to normal life style. Recent fracture(<6months) have high fusion rate of 90% with this approach and for remote fracture(≥18months) it reduces to 25%. Here we present a case report of 18 years old female with type II odontoid fracture and underwent anterior transcervical lag screw fixation under C-arm guidance.